A defucosylated bispecific multivalent molecule exhibits broad HIV-1-neutralizing activity and enhanced antibody-dependent cellular cytotoxicity against reactivated HIV-1 latently infected cells. (24th August 2018) - Kong, Desheng; Wang, Yan; Ji, Ping; Li, Wei; Ying, Tianlei; Huang, Jinghe; Wang, Chen; Wu, Yanling; Wang, Yanping; Chen, Weizao; Hao, Yanling; Hong, Kunxue; et al.
Abstract : Objective: Current treatments cannot completely eradicate HIV-1 owing to the presence of latently infected cells, which harbor transcriptionally silent HIV-1. However, defucosylated antibodies can readily kill latently infected cells after their activation to express envelope glycoprotein (Env) through antibody-dependent cellular cytotoxicity (ADCC). We herein aimed to test a defucosylated bispecific multivalent molecule consisting of domain-antibody and single-domain CD4, LSEVh-LS-F, for its HIV-1 neutralizing activity and ADCC against the reactivated latently infected cells, compared with the nondefucosylated molecule LSEVh-LS. Methods: LSEVh-LS-F's neutralizing activity against a panel of newly characterized Chinese HIV-1 clinical isolates was assessed by using TZM-bl-based and PBMC-based assays. LSEVh-LS-F-mediated ADCC in the presence of natural killer cells against cell lines that stably express Env proteins, HIV-1-infected cells and LRA-reactivated HIV-1 latent cells, was measured using a lactate dehydrogenase (LDH) cytotoxicity assay or flow cytometry. Results: LSEVh-LS-F and LSEVh-LS were equally effective in neutralized infection of all HIV-1 isolates tested with IC50 and IC90 values 3∼4-fold lower than those of VRC01. LSEVh-LS-F was more effective in natural killer-mediated killing of HIV-1 Env-expressing cell lines, HIV-1-infected cells, latency reactivation agents-reactivated ACH2 cells and reactivated latently infected resting CD4 + T cell line as well as resting CD4 + T lymphocytes isolated from patients receiving HAART. Conclusion: LSEVh-LS-F exhibits broad HIV-1 neutralizing activity and enhanced ADCC against HIV-1-infected cells, reactivated latently infected cell lines and primary CD4 + T cells, thus being a promising candidate therapeutic for eradicating the HIV-1 reservoir. Abstract : Supplemental Digital Content is available in the text